2021
DOI: 10.1097/mlr.0000000000001555
|View full text |Cite
|
Sign up to set email alerts
|

County-level Predictors of Growth in Community-based Primary Care Use Among Veterans

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 22 publications
2
20
0
Order By: Relevance
“…Similarly, rural VA patients with a new diagnosis of depression, anxiety, or posttraumatic stress disorder in 2004 were less likely to receive psychotherapy than urban VA patients, 24 but a follow-up study indicated the disparity began to close between 2007 and 2010. 25 With regard to expansion of VA-paid care in the community, there were several recent studies in a special issue of Medical Care that compared changes to access for rural versus urban patients and showed that access and timeliness generally improved for rural patients who received both VA-delivered or VA-paid care between 2015 and 2018, 26,27 but none of that work was focused specifically on mental health care. 28 Thus, there is no longitudinal study that examines changes in access to mental health services for rural VA patients following implementation of the UMHSP and subsequent expansion of VA-paid care in the community.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, rural VA patients with a new diagnosis of depression, anxiety, or posttraumatic stress disorder in 2004 were less likely to receive psychotherapy than urban VA patients, 24 but a follow-up study indicated the disparity began to close between 2007 and 2010. 25 With regard to expansion of VA-paid care in the community, there were several recent studies in a special issue of Medical Care that compared changes to access for rural versus urban patients and showed that access and timeliness generally improved for rural patients who received both VA-delivered or VA-paid care between 2015 and 2018, 26,27 but none of that work was focused specifically on mental health care. 28 Thus, there is no longitudinal study that examines changes in access to mental health services for rural VA patients following implementation of the UMHSP and subsequent expansion of VA-paid care in the community.…”
Section: Introductionmentioning
confidence: 99%
“…Care leakage from health systems can lead to poor‐quality health care, adverse health outcomes, and high costs for both patients and systems. Past studies found that chronic illness, rurality, longer in‐house wait times, longer distance to in‐house care, unavailability of certain specialties in house, and perceptions of quality are associated with patients seeking out‐of‐system care 2,4,13,30 . Health system administrators have limited control over these factors.…”
Section: Discussionmentioning
confidence: 99%
“…Past studies found that chronic illness, rurality, longer inhouse wait times, longer distance to in-house care, unavailability of certain specialties in house, and perceptions of quality are associated with patients seeking out-of-system care. 2,4,13,30 Health system administrators have limited control over these factors. However, few studies examined the impact of potentially modifiable factors on care leakage from integrated health systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,14 Prior work on CC has typically taken the networks as given and studied the program's association with access to care and compared quality and cost outcomes between VHA and non-VHA physicians. [15][16][17][18][19][20][21] These studies have found that VHA care is typically as good as care from non-VHA physicians, but it is less clear whether policies such as the MISSION Act have improved access. 21 Additionally, some studies have found significant differences in quality and access across facilities and geographic regions.…”
Section: Introductionmentioning
confidence: 99%